INDONESIA'S EFFORTS TO INCREASE TUNA EXPORTS TO GERMANY - Maharani, Suci; Retnaningsih, Umi O. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Tuna is one of the prospective fishery commodity for exports due to high demand in the international market. However, European Union as the main buyer demand its imports to comply with Council Regulation. This tariff and non-tariff barriers on Indonesia can cause a decline for the exports. To maintain its market Indonesia should find ways since Germany is the fourth largest tuna importer in the world. Efforts by Indonesian government to maintain tuna exports to Germany will be described in this study.This research uses descriptive qualitative method. The perspective used by the author in this thesis is the perspective of liberalism with the level of nation state analysis, and the theory used is the theory of international trade. To analyze this case, the authors collected data from books, journals, websites, dictionaries, as well as various information from the EUR-Lex, the Ministry of Trade of the Republic of Indonesia, the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia and the Association of Pole and Line & Handline Indonesia (AP2HI) regarding Indonesia's efforts to increase fish exports tuna to Germany.The results of this study indicate that Indonesia seeks to increase tuna exports to Germany by lobbying with the European Union regarding reducing tuna export tariffs, improving quality and cleanliness in the management of Indonesian tuna, and eradicating illegal fishing. Indonesia is still working on increasing tuna exports to Germany. Although there has not been an increase in the export value, there has been an increase in the quality of tuna so that it can increase the confidence of the European Union, especially Germany, in Indonesian tuna.Keywords: Effort, Tariff Barriers, Non-Tariff Barriers, Tuna, Exports, International Trade